Health education in the light of Pope John Paul II - Zofia Kubińska; Helena Konowaluk-Nikitin (Rozprawy Społeczne)
Abstract The Authors discussed the basic truths of Pope John Paul II's personalistic philosophy, upbringing in the light of the philosophy of christian personalism and the significance of educational values in the Pope's teachings.